GC–MS analysis of the regioisomeric methoxy- and methyl-benzoyl-1-pentylindoles: Isomeric synthetic cannabinoids. Issue 5 (September 2015) - Abdel-Hay, Karim M.; DeRuiter, Jack; Smith, Forrest; Belal, Tarek S.; Clark, C. Randall
Abstract: The regioisomeric 1-n-pentyl-3-(methoxybenzoyl)indoles and the 1-n-pentyl-3-(methylbenzoyl)indoles represent potential designer modifications in the synthetic cannabinoid drug category. These six compounds were prepared by a two-step synthetic method. The analytical properties and methods of regioisomeric differentiation were developed in this study. The molecular ion represents the base peak in the EI mass spectra for most of the compounds in this group. The meta- and para-isomers in each series display fragment ions at equivalent masses with some differences in relative abundance of these ions. The ortho-substituted isomers for both the methoxybenzoyl and methylbenzoyl series show a unique fragment ion occurring at M-17. Deuterium labeling for the methoxy group in the ortho-methoxybenzoyl isomer (ortho-OCD3 ) confirmed the ortho-substituent as the source of the hydrogen in OH (M-17) elimination. The two sets of regioisomers were well resolved by capillary gas chromatography and the elution order reflected increasing molecular linearity. In both sets of compounds the ortho-isomer eluted first and the para-isomer showed the highest retention time. The HPLC separation showed the ortho-isomer eluting first and the meta-isomer eluting last in both sets of regioisomers. Graphical abstract: Highlights: Three regioisomeric methylbenzoyl-1-n-pentylindoles and three methoxybenzoyl-1-n-pentylindoles were prepared in this study. The MS of these meta- and para-substituted benzoyl-1-n-pentylindoles show similar major fragment ions. The ortho-substituted methoxy and methylbenzoyl isomers show a unique MS fragment at (M-17). Deuterium labeling identified the ortho-methoxy group as the source of the hydrogen for the loss of the (M-17) OH group. Each set of three regioisomeric compounds were separated by capillary GC.